Body Composition in Crohn’s Disease and Ulcerative Colitis: Correlation with Disease Severity and Duration - Dawesh P. Yadav; Saurabh Kedia; Kumble Seetharama Madhusudhan; Sawan Bopanna; Sandeep Goyal; Saransh Jain; Naval K. Vikram; Raju Sharma; Govind K. Makharia; Vineet Ahuja (Canadian Journal of Gastroenterology and Hepatology)
Background. Results on body composition in Crohn’s disease (CD) and ulcerative colitis (UC) have been heterogeneous and are lacking from Asia. Present study assessed body composition in CD/UC and correlated it with disease severity/duration. Methods. Patients of CD/UC following between Dec 2014 and Dec 2015 who consented for bioimpedance analysis for body fat measurement were included. Lean mass and fat-free mass index (FFMI) were calculated with standard formulae. Visceral fat area (VFA), subcutaneous fat area (SCA), and visceral to subcutaneous fat ratio (VF/SC) were evaluated in CD patients on abdominal CT. Results. Lean mass in CD (n=44, mean age: 41.2±15.8 years, 73% males) was significantly lower than UC (n=53, mean age: 33.2±11.2 years, 68% males; 44.2±7.8 versus 48.3±8.4 Kg, p=0.01). In both UC/CD, disease severity was associated with nonsignificant decline in BMI (UC: 22.1±4.9 versus 20.2±3.2 versus 19.9±3.2 kg/m2, p=0.23; CD: 22.1±4.2 versus 19.9±2.3 versus 19.7±4.2 kg/m2, p=0.18) and fat mass (UC: 10.9±8.9 versus 8.1±5.9 versus 5.7±3.6 kg, p=0.14; CD: 11.2±7 versus 7.9±4.4 versus 7.2±5.9 kg, p=0.16), and disease duration was associated with significant decline in FFMI (p<0.05). In CD, disease severity was associated with nonsignificant decline in SCA and increase in VF/SC. Conclusions. CD patients have lower lean mass than UC. Body fat decreases with increasing disease severity and fat-free mass decreases with increasing disease duration in both UC/CD.